Thinking and Feeling: Individual Differences in Habitual Emotion Regulation and Stress-Related Mood Are Associated With Prefrontal Executive Control. (January 2017) - Scult, Matthew A.; Knodt, Annchen R.; Swartz, Johnna R.; Brigidi, Bartholomew D.; Hariri, Ahmad R.
Calculating math problems from memory may seem unrelated to everyday processing of emotions, but they have more in common than one might think. Prior research highlights the importance of the dorsolateral prefrontal cortex (dlPFC) in executive control, intentional emotion regulation, and experience of dysfunctional mood and anxiety. Although it has been hypothesized that emotion regulation may be related to "cold" (i.e., not emotion-related) executive control, this assertion has not been tested. We address this gap by providing evidence that greater dlPFC activity during cold executive control is associated with increased use of cognitive reappraisal to regulate emotions in everyday life. We then demonstrate that in the presence of increased life stress, increased dlPFC activity is associated with lower mood and anxiety symptoms and clinical diagnoses. Collectively, our results encourage ongoing efforts to understand prefrontal executive control as a possible intervention target for improving emotion regulation in mood and anxiety disorders.